2007
DOI: 10.1111/j.1538-7836.2007.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous expression of Bcl‐xL protein during megakaryopoiesis is post‐translationally regulated by thrombopoietin‐mediated Akt activation, which prevents the cleavage of Bcl‐xL

Abstract: Summary.  Background: One of the important biological activities of thrombopoietin (TPO) is to prevent the apoptosis of megakaryocytes. As the antiapoptotic protein Bcl‐xL, which has been proven to be indispensable for erythroid differentiation, is also abundantly expressed in megakaryocytes, it is assumed that Bcl‐xL plays an important role in megakaryopoiesis. Objectives: We investigated the expression of Bcl‐xL during megakaryopoiesis and the underlying regulatory mechanism. Methods and Results: In stem cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…With regard to Bcl-xL, previous in-vitro studies reported not only its expression profile during megakaryocyte differentiation but also its anti-apoptotic involvement. 10,31 This agrees with our in-vitro study showing moderate apoptosis of megakaryoblastic cells upon ABT-737 treatment (Figures 5b-e). On the other hand, in in-vivo settings, Josefsson et al 16 very recently analyzed this in detail and reported that Bcl-xL played an important role in preventing mature megakaryocytes from apoptosis at the proplatelet formation stage but was not required for their growth and development.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…With regard to Bcl-xL, previous in-vitro studies reported not only its expression profile during megakaryocyte differentiation but also its anti-apoptotic involvement. 10,31 This agrees with our in-vitro study showing moderate apoptosis of megakaryoblastic cells upon ABT-737 treatment (Figures 5b-e). On the other hand, in in-vivo settings, Josefsson et al 16 very recently analyzed this in detail and reported that Bcl-xL played an important role in preventing mature megakaryocytes from apoptosis at the proplatelet formation stage but was not required for their growth and development.…”
Section: Discussionsupporting
confidence: 82%
“…We next investigated the involvement of Bcl-xL, another anti-apoptotic Bcl-2 family protein known to exist in megakaryocytes, 10 in the development and survival of the megakaryocytic lineage. We used previously generated megakaryocytic lineage-specific homozygote Bcl-xL knockout mice (bcl-x flox/flox pf4-cre), 15 which presented with severe thrombocytopenia due to massive platelet apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Furthermore, bcl-2-or bcl-xL-transfected MKs, which should be resistant to caspase-3 activation, were reported to be significantly less capable of forming proplatelets. 9,10 Contrary to these findings, our recent in vitro and in vivo observations suggested that Bcl-xL protein is highly expressed throughout megakaryopoiesis until the platelet-producing late stage of maturation, 11 which raised the question about the apoptosis theory of platelet production. On the other hand, recent studies have established that caspase activation is involved in nonapoptotic cellular functions, such as the proliferation and differentiation of various types of cells.…”
Section: Introductionmentioning
confidence: 88%
“…If megakaryocytes are susceptible to activation of the intrinsic pathway to apoptosis, then one would expect that one or more members of the Bcl-2 family of prosurvival proteins must keep Bak and Bax in check to maintain cellular integrity. Given the known role of one such prosurvival, Bcl-x L , in regulating platelet life span (Mason et al, 2007), and given its documented expression in megakaryocytes (Terui et al, 1998;Sanz et al, 2001;Kozuma et al, 2007), we generated a megakaryocyte-specific deletion of Bcl-x. Mice harboring a (Fig.…”
mentioning
confidence: 99%